Isokinetic strength and endurance after percutaneous and open surgical repair of Achilles tendon ruptures - Goren, David; Ayalon, Moshe; Nyska, Meir (Foot & ankle international, 2005)
Reports on complete spontaneous Achilles tendon ruptures and associated treatment have become more frequent in the literature in the past two decades, as has the request for treatments that enable the finest possible functional recovery. The best available treatment is a matter of considerable controversy in the literature. The purpose of this study was to compare the isokinetic strength and endurance of the plantarflexor muscle-tendon unit in subjects who sustained rupture of the Achilles tendon and underwent either open surgery or closed percutaneous repair of the Achilles tendon. Twenty patients (18 males, 2 females) with spontaneous ruptures of the Achilles tendon were included in this study. Ten patients were treated by open surgery, and 10 patients were treated percutaneously. All patients had ruptured their Achilles tendon more than 6 months before the study, and all of the ruptures occurred 3.5 years or less before the day of the testing. All patients underwent an oriented physical examination. An isokinetic Biodex dynamometer (Biodex Medical System, Shirley, NY) was used to measure ankle joint angle, and in plantarflexion to calculate the torque at the ankle joint (Newton/meter), and the average work (jouls) for both maximal power and endurance. Each measurement was compared to the normal ankle. Biodex dynamometer evaluations at 90 deg/sec demonstrated a significant difference of maximal voluntary plantarflexor torque, endurance performance and range of motion at the ankle joint between the involved and uninvolved sides in patients treated by either mode of treatment. Yet, no statistically significant differences were revealed for the parameters mentioned above between the subjects that were treated either percutaneously or by an open surgery. In functional terms, the biomechanical outcomes of open surgery and percutaneous repair for acute ruptures of the Achilles tendon are both effective.